Religion and National Identities in an Enlarged Europe
XII, 187 p.
Keywords: This volume analyzes changing relationships between religion and national identity in the course of European integration. Examining elite discourse, media debates and public opinions across Europe over a decade, it explores how accelerated European integration and Eastern enlargement have affected religious markers of collective identity.